Principal-Led Clinical Supervision in Indonesian Schools: Advancing Teacher Professional Development for SDG 4 - Akhmad Mundir; Andi Kristanto; Amrozi Khamidi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To investigate the impact of principals' clinical supervision on teachers' pedagogical competence within the cultural context of Indonesian schools. Clinical supervision has been shown to promote reflective practice. However, its implementation in Indonesia is often a formality to meet government-set management standards, rather than a means of developing teachers' competencies. Method: To use a convergent mixed-methods research design and involved eighty-nine teachers and six principals from six elementary and junior high schools in Jombang, East Java. Quantitative data, derived from pre- and post supervision. Result: After clinical supervision, showed statistically significant improvements in teachers' pedagogical skills. The most substantial improvements were seen in teachers' lesson planning and evaluation. Qualitatively, thematic analysis found that teachers initially experienced